2017
DOI: 10.1038/srep46181
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces progenitor cell death, microglia activation, and blood-brain barrier damage in the juvenile rat cerebellum

Abstract: Posterior fossa tumors are the most common childhood intracranial tumors, and radiotherapy is one of the most effective treatments. However, irradiation induces long-term adverse effects that can have significant negative impacts on the patient’s quality of life. The purpose of this study was to characterize irradiation-induced cellular and molecular changes in the cerebellum. We found that irradiation-induced cell death occurred mainly in the external germinal layer (EGL) of the juvenile rat cerebellum. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 54 publications
(70 reference statements)
6
36
0
Order By: Relevance
“…Radioprotective effect of MZC against brain NS induced by ionizing radiation was accomplished only at lower dose of 2Gy in hippocampus and cortex, but not in cerebellum (Figure 3). This is in line with the results from a recent study indicating that lower doses of irradiation increased blood-brain barrier (BBB) permeability, decreased blood flow and content of antioxidants in the cerebellum, more than in other brain regions, causing OS [36].…”
Section: Discussionsupporting
confidence: 92%
“…Radioprotective effect of MZC against brain NS induced by ionizing radiation was accomplished only at lower dose of 2Gy in hippocampus and cortex, but not in cerebellum (Figure 3). This is in line with the results from a recent study indicating that lower doses of irradiation increased blood-brain barrier (BBB) permeability, decreased blood flow and content of antioxidants in the cerebellum, more than in other brain regions, causing OS [36].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that irradiation, with accompanying monocyte in ltration, has lasting effects on BBB integrity (50,(54)(55)(56). Despite an observed in ux of peripheral-derived myeloid cells, BBB integrity was not compromised, as assessed by Prussian blue, IgG, and brinogen staining ~ 10mo postirradiation ( Fig.…”
Section: Lasting Effects Of Irradiation On Bbb Integrity Neurogenesimentioning
confidence: 80%
“…Here, our data show that CSF1R inhibition following whole body irradiation results in the near complete (~ 80%) replacement of microglia with monocytes. Previous data has shown that microglia survive cranial irradiation, however, do exhibit increased activation and decreased cell number (73); and that irradiation induces loss of proliferating cells, including progenitor/stem and microglial cells (55). Thus, in order to induce complete monocyte engraftment, it appears that the brain must possess an empty microglial niche or microglial cells that lack the ability to proliferate/self-renew.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we used female rats as the irradiation animal model, and in this study we found that brain irradiation in juvenile female rats led to greater weight gain with age, particularly from 15 weeks after irradiation. Such a greater weight gain did not occur in our previous irradiation studies with male rats [4, 24]. With the aim of further characterizing the weight changes, we evaluated the BMI and abdominal circumference, and these two indicators also increased significantly with age in female rats after juvenile brain irradiation.…”
Section: Discussionmentioning
confidence: 99%